MXene composite corrosion inhibitor as well as preparation method and application thereof
By using the MXENE composite erosion agent, the problem of long etching time, low zinc recovery rate, poor steel corrosion effect, and high cost of hot -dip galvanized plate recovery have achieved efficient and economic zinc recovery effects.
Patent Information
- Application Number
- CN202411371362.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing corrosion inhibitors used for hot-dip galvanized sheet recovery have problems such as long etching time, low zinc recovery rate, poor corrosion inhibition effect of steel and high cost.
Adopt MXENE composite corrosion agent, mix MXENE powder with Liuya methyleneramine in aquatic ethanol, react in double steaming water, combined with additives for secondary ultrasound treatment, and finally add hydrochloric acid solution to prepare mxene compound slow slowly Eclipse.
The efficient erosion of zinc element in the hot -dip galvanized layer, at the same time, effectively prevent the erosion of the iron element in the steel plate, shorten the erosion time, increase the zinc recovery rate, and reduce the cost.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal corrosion inhibitors, and in particular to a MXene composite corrosion inhibitor and a preparation method and application thereof. Background Art
[0002] Hot-dip galvanized sheet is a steel sheet coated with a hot-dip galvanized layer by hot-dip plating process. Through the reaction and diffusion between iron and zinc, the hot-dip galvanized layer is uniform and dense, and has strong bonding with the steel sheet. Compared with other metal protection methods, the hot-dip galvanized layer has incomparable advantages in durability, maintenance-free and economy. It can greatly delay the corrosion of steel sheets and is widely used in automobiles, ships, electrical appliances and other equipment. However, when these equipment reach the end of their service life, due to the uniform and dense hot-dip galvanized layer and strong bonding, it is difficult for zinc elements to separate from the steel sheet. The recycling cost of hot-dip galvanized sheet is high, the zinc recovery rate is low, and there are great difficulties in reuse.
[0003] Usually, the recycling and reuse of hot-dip galvanized sheets is achieved through the method of hydrochloric acid etching. However, when hydrochloric acid is used to recover the hot-dip galvanized layer, it is inevitable that the internal steel plate will be corroded. How to achieve both efficient etching of the galvanized layer and ensuring corrosion inhibition of the internal steel plate when recycling hot-dip galvanized sheets has become a difficult problem. At present, organic corrosion inhibitors with dezincification effects have also been developed on the market, but there are problems such as long etching time for hot-dip galvanized sheets (about 1h), poor iron corrosion inhibition effect (the remaining iron content in steel is about 60%), low zinc recovery rate (below 95%), high cost, etc. Therefore, it is urgent to provide a steel corrosion inhibitor with a high zinc recovery rate for hot-dip galvanized sheet recycling. Summary of the invention
[0004] In view of the problems that the existing corrosion inhibitors used for hot-dip galvanized sheet recovery have long etching time, low zinc recovery rate, poor steel corrosion inhibition effect and high cost, the present invention provides a MXene composite corrosion inhibitor and a preparation method and application thereof.
[0005] In a first aspect, the present invention provides a method for preparing a MXene composite corrosion inhibitor, comprising the following steps: (1) Mix MXene powder and hexamethylenediamine in a mass ratio of 1:5-10, add them into anhydrous ethanol, stir, and ultrasonicate for 30-60 minutes to obtain a MXene powder mixed solution; (2) The MXene powder mixture obtained in step (1) is mixed with 10-15 L of double distilled water, and reacted in a reactor at a temperature of 150-180° C. for 2-5 h to obtain a MXene mixed solution. The MXene mixed solution and the additive are mixed in a mass ratio of 2-5:1 and then subjected to a secondary ultrasonic treatment for 30-40 min to obtain a MXene composite corrosion inhibitor intermediate solution; (3) Mixing the intermediate solution of the MXene composite corrosion inhibitor with double distilled water at a volume ratio of 1:14-20, and then adding a hydrochloric acid solution with a concentration of 5.0%-10.0% to obtain the MXene composite corrosion inhibitor; Wherein, in step (1), the mass volume ratio of MXene powder and anhydrous ethanol is 10-30 g: 2-5 L; In step (2), the additive is selected from one or more of 8-hydroxyquinoline, 2-mercaptobenzothiazole, 5-amino-1,3,4-thiadiazole-2-thiol, calcium phosphate, cerium nitrate and sodium molybdate; In step (3), the volume ratio of the MXene composite corrosion inhibitor intermediate solution to the hydrochloric acid solution is 1:20-40.
[0006] Furthermore, the preparation method of MXene powder in step (1) is to mix lithium fluoride with a 36% hydrochloric acid solution and then add Ti 3 AlC 2 , ultrasonic and magnetic stirring were performed successively, and then double distilled water was added for washing. After washing, the pH of the solution was raised to 6 for centrifugation. The upper clear liquid was the MXene initial solution. The MXene initial solution was mixed with anhydrous ethanol and then double distilled water was added for washing. MXene powder was obtained by freeze-drying.
[0007] Furthermore, the mass volume ratio of lithium fluoride to hydrochloric acid solution is 20-50g:3-10L.
[0008] Furthermore, lithium fluoride and Ti 3 AlC 2 The mass ratio is 2-5:15-30.
[0009] Furthermore, the ultrasonic time is 20-30 min; the temperature of the magnetic stirring is 40° C., and the time is 12-24 h.
[0010] Furthermore, the MXene initial solution was mixed with anhydrous ethanol in a volume ratio of 3-5:1 and reacted at 50-60 °C for 1-5 h.
[0011] Furthermore, in step (2), the additive is 8-hydroxyquinoline, 2-mercaptobenzothiazole or cerium nitrate.
[0012] In a second aspect, the present invention provides a MXene composite corrosion inhibitor prepared by the above preparation method.
[0013] In a third aspect, the present invention provides an application of the above-mentioned MXene composite corrosion inhibitor for corrosion and dezincification on hot-dip galvanized sheet.
[0014] Furthermore, the etching and dezincification time is 12 min.
[0015] The beneficial effects of the present invention are: The present invention provides a method for preparing a MXene composite corrosion inhibitor, which is simple to operate, has low raw material cost, and MXene as the main raw material has many active sites, a large active area, and is easy to adsorb on the surface of steel. The obtained MXene composite corrosion inhibitor can not only realize the corrosion of zinc elements in hot-dip galvanized layers, but also effectively hinder the corrosion of iron elements in steel plates. The etching time is about one-fifth of the existing organic corrosion inhibitors, which is time-saving and efficient. Energy spectrum detection found that under the same conditions, compared with hydrochloric acid solution, the MXene composite corrosion inhibitor provided by the present invention was used to etch hot-dip galvanized plates, and the amount of iron element corrosion was greatly reduced, while the amount of zinc element corrosion was equivalent to the effect of hydrochloric acid etching, which shows that the MXene composite corrosion inhibition solution greatly reduces the corrosion of steel plates while etching zinc, and effectively achieves corrosion inhibition of iron elements. DETAILED DESCRIPTION
[0016] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0017] Example 1 A method for preparing a MXene composite corrosion inhibitor comprises the following steps: 1. Preparation of MXene powder (1) Mix 20g of lithium fluoride powder with 3L of hydrochloric acid solution (36%) to obtain a clear solution, and then add 150g of MAX (Ti 3 AlC 2 ), ultrasonic stirring for 20 minutes, after MAX is evenly dispersed, magnetic stirring is performed at 40°C for 12 hours, and double distilled water is added for washing after the reaction, until the pH of the solution after washing increases to 6, and then centrifugation is performed, and the upper clear liquid is taken to obtain the MXene initial solution; (2) The MXene initial solution was mixed with anhydrous ethanol in a volume ratio of 5:1 and reacted at 50 °C for 1 h to obtain a MXene secondary solution; (3) The MXene secondary solution was washed with double distilled water and freeze-dried for 24 h to obtain the product MXene powder.
[0018] 2. Preparation of MXene composite corrosion inhibitor (1) Weigh 10 g of MXene powder and 50 g of hexamethylenediamine, mix them in a mass ratio of 1:5, then add them to 2 L of anhydrous ethanol solution, stir for 30 min to obtain a mixed solution, and ultrasonicate for 30 min to obtain a MXene powder mixed solution; (2) Add 10 L of double distilled water to the MXene powder mixture, pour it into a reactor, raise the temperature to 180 °C at a rate of 2 °C / min, and react for 3 h to obtain a MXene mixed solution. Mix the MXene mixed solution with 2-mercaptobenzothiazole and perform a secondary ultrasonic treatment. The ultrasonic time is 40 min. The mass ratio of the MXene mixed solution to 2-mercaptobenzothiazole is 4:1 to obtain a MXene composite corrosion inhibitor intermediate solution. (3) Take 5 L of the MXene composite corrosion inhibitor intermediate solution, add 70 L of double distilled water to dilute and mix, and then add 150 L of 10.0% hydrochloric acid to obtain the MXene composite corrosion inhibitor.
[0019] Example 2 A method for preparing a MXene composite corrosion inhibitor comprises the following steps: 1. Preparation of MXene powder (1) Mix 50g of lithium fluoride powder with 5L of hydrochloric acid solution (36%) to obtain a clear solution, and then pour 300g of MAX (Ti 3 AlC 2 ), ultrasonic stirring for 20 minutes, after the MAX phase is evenly dispersed, magnetic stirring is performed at 40°C for 18 hours, and double distilled water is added for washing after the reaction, until the pH of the solution after washing increases to 6.5, and then centrifugation is performed, and the upper clear liquid is taken to obtain the MXene initial solution; (2) The MXene initial solution was mixed with anhydrous ethanol in a volume ratio of 5:1 and reacted at 60 °C for 1 h to obtain a MXene secondary solution; (3) The MXene secondary solution was washed with double distilled water and freeze-dried for 18 h to obtain the product MXene powder.
[0020] 2. Preparation of MXene composite corrosion inhibitor (1) Weigh 20 g of MXene powder and 200 g of hexamethylenediamine, mix them in a mass ratio of 1:10, then add them to 5 L of anhydrous ethanol solution, stir for 30 min to obtain a mixed solution, and ultrasonicate for 60 min to obtain a MXene powder mixed solution; (2) Add 15 L of double distilled water to the MXene powder mixture, pour it into a reactor, raise the temperature to 150 °C at a rate of 2 °C / min, and react for 2 h to obtain a MXene mixed solution. Mix the MXene mixed solution with 8-hydroxyquinoline and perform a secondary ultrasonic treatment. The ultrasonic time is 30 min. The mass ratio of the MXene mixed solution to 2-mercaptobenzothiazole is 2:1 to obtain a MXene composite corrosion inhibitor intermediate solution. (3) Take 5 L of the MXene composite corrosion inhibitor intermediate solution, add 100 L of double distilled water to dilute and mix, and then add 200 L of 5.0% hydrochloric acid to obtain the MXene composite corrosion inhibitor.
[0021] Example 3 A method for preparing a MXene composite corrosion inhibitor comprises the following steps: 1. Preparation of MXene powder (1) Mix 50g of lithium fluoride powder with 10L of hydrochloric acid solution (36%) to obtain a clear solution, and then pour 300g of MAX (Ti 3 AlC 2 ), ultrasonic stirring for 20 minutes, after the MAX phase is evenly dispersed, magnetic stirring is performed at 40°C for 24 hours, and double distilled water is added for washing after the reaction, until the pH of the solution after washing increases to 6, and then centrifugation is performed, and the upper clear liquid is taken to obtain the MXene initial solution; (2) The MXene initial solution was mixed with anhydrous ethanol in a volume ratio of 5:1 and reacted at 60 °C for 5 h to obtain a MXene secondary solution; (3) The MXene secondary solution was washed with double distilled water and freeze-dried for 24 h to obtain the product MXene powder.
[0022] 2. Preparation of MXene composite corrosion inhibitor (1) Weigh 30 g of MXene powder and 150 g of hexamethylenediamine, mix them in a mass ratio of 1:5, then add them to 5 L of anhydrous ethanol solution, stir for 30 min to obtain a mixed solution, and ultrasonicate for 60 min to obtain a MXene powder mixed solution; (2) Add 15 L of double distilled water to the MXene powder mixture, pour it into a reactor, raise the temperature to 160 °C at a rate of 2 °C / min, and react for 5 h to obtain a MXene mixed solution. Mix the MXene mixed solution with cerium nitrate and perform a secondary ultrasonic treatment. The ultrasonic time is 30 min. The mass ratio of the MXene mixed solution to 2-mercaptobenzothiazole is 5:1 to obtain a MXene composite corrosion inhibitor intermediate solution. (3) Take 5 L of the MXene composite corrosion inhibitor intermediate solution, add 100 L of double distilled water to dilute and mix, and then add 200 L of 5.0% hydrochloric acid to obtain the MXene composite corrosion inhibitor.
[0023] Experimental Example 1 Four hot-dip galvanized sheets of the same size were taken and immersed in the same amount of the MXene composite corrosion inhibitor prepared in Examples 1-3, and the waste hot-dip galvanized sheets were etched for 12 minutes to complete the recycling and reuse of the waste hot-dip galvanized sheets. The hot-dip galvanized sheets were taken out, and the contents of Fe, Zn, and Al etched by the MXene composite corrosion inhibitor were detected using an inductively coupled plasma mass spectrometer (ICP), and a 15% hydrochloric acid solution was used to replace the MXene composite corrosion inhibitor for a comparative test. The test results are shown in Table 1.
[0024] Table 1 Comparison of Fe, Zn and Al contents in Examples 1-3 MXene composite corrosion inhibitor and hydrochloric acid solution
[0025] From the results in Table 1, it can be seen that compared with the hydrochloric acid solution, after the MXene composite corrosion inhibitor of Examples 1-3 was used to treat the waste hot-dip galvanized sheet, the iron corrosion amount was greatly reduced, while the zinc corrosion amount was not much different, indicating that the MXene composite corrosion inhibitor can effectively erode zinc while greatly reducing the corrosion of the steel sheet and improving the recovery rate of the hot-dip galvanized sheet.
[0026] Although the present invention has been described in detail by way of preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and such modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily conceive of changes or substitutions within the technical scope disclosed by the present invention, and such changes or substitutions shall be within the scope of protection of the present invention.
Claims
1. A method for preparing a MXene composite corrosion inhibitor, characterized in that: The steps include: (1) Mix MXene powder and hexamethylenediamine in a mass ratio of 1:5-10, add them into anhydrous ethanol, stir, and ultrasonicate for 30-60 minutes to obtain a MXene powder mixed solution; (2) The MXene powder mixture obtained in step (1) is mixed with 10-15 L of double distilled water, and reacted in a reactor at a temperature of 150-180° C. for 2-5 h to obtain a MXene mixed solution. The MXene mixed solution and the additive are mixed in a mass ratio of 2-5:1 and then subjected to a secondary ultrasonic treatment for 30-40 min to obtain a MXene composite corrosion inhibitor intermediate solution; (3) Mixing the intermediate solution of the MXene composite corrosion inhibitor with double distilled water at a volume ratio of 1:14-20, and then adding a hydrochloric acid solution with a concentration of 5.0%-10.0% to obtain the MXene composite corrosion inhibitor; Wherein, in step (1), the mass volume ratio of MXene powder and anhydrous ethanol is 10-30 g: 2-5 L; In step (2), the additive is selected from one or more of 8-hydroxyquinoline, 2-mercaptobenzothiazole, 5-amino-1,3,4-thiadiazole-2-thiol, calcium phosphate, cerium nitrate and sodium molybdate; In step (3), the volume ratio of the MXene composite corrosion inhibitor intermediate solution to the hydrochloric acid solution is 1:20-40.
2. The method for preparing a MXene composite corrosion inhibitor according to claim 1, characterized in that: The preparation method of MXene powder in step (1) is as follows: lithium fluoride is mixed with a hydrochloric acid solution with a concentration of 36%, and then Ti3AlC2 is added, followed by ultrasonic and magnetic stirring, and then double distilled water is added for washing. After washing, the pH of the solution is increased to 6 and centrifuged. The upper clear liquid is the MXene initial solution. The MXene initial solution is mixed with anhydrous ethanol for reaction, and then double distilled water is added for washing, and freeze-drying is performed to obtain MXene powder.
3. The method for preparing a MXene composite corrosion inhibitor according to claim 2, characterized in that: The mass volume ratio of lithium fluoride and hydrochloric acid solution is 20-50g:3-10L.
4. The method for preparing a MXene composite corrosion inhibitor according to claim 2, characterized in that: The mass ratio of lithium fluoride to Ti3AlC2 is 2-5:15-30.
5. The method for preparing a MXene composite corrosion inhibitor according to claim 2, characterized in that: The ultrasonic time is 20-30 minutes; the magnetic stirring temperature is 40°C and the time is 12-24 hours.
6. The method for preparing a MXene composite corrosion inhibitor according to claim 2, characterized in that: The MXene initial solution was mixed with anhydrous ethanol in a volume ratio of 3-5:1 and reacted at 50-60 °C for 1-5 h.
7. The method for preparing a MXene composite corrosion inhibitor according to claim 1, characterized in that: The additive in step (2) is 8-hydroxyquinoline, 2-mercaptobenzothiazole or cerium nitrate.
8. A MXene composite corrosion inhibitor prepared by the preparation method as claimed in claim 1.
9. An application of the MXene composite corrosion inhibitor as claimed in claim 8 for corrosion and dezincification on hot-dip galvanized sheet.
10. The use according to claim 9, characterized in that The time of etching and dezincification is 12 minutes.
Citation Information
Patent Citations
Preparation method of MXene / CeO2 composite material
CN108704637A
CeO2 / MXene composite two-dimensional material as well as preparation method and application thereof
CN112704736A
MXene-based composite material for improving performance of lithium-sulfur battery diaphragm and preparation method of MXene-based composite material
CN115504473A
Preparation method of high-performance flow battery composite membrane based on MXene
CN117096369A
Efficient magnesium alloy corrosion inhibitor and preparation method thereof
CN118600430A
Cited By
Etching solution and preparation method thereof
CN121203666A
An etching solution and its preparation method
CN121203666B